The Alloga quarry, Southwestern Sinai, Egypt: geological studies, radioactivity and mineralogical investigations. Issue 1 (1st January 2020) - Sallam, Osama R.; Abdrabboh, Ahmad M.; Abbas, Abd Elhadi A.; Ali, Hani H.; Alshami, Abdalla S.
ABSTRACT: Gabal Alloga area is located in the southwestern part of the Sinai Peninsula. It represents one of the more significant economic and uranium mineralized areas. It is located within a low basin and most of the high radioactive anomalies recorded in the sediments of Um Bogma Formation within this basin. The Lower Carboniferous Um Bogma Formation is the main rock units constituting the face wall of the Allouga quarry. The wall shows very high radioactivity with eU-contents reaches 3000 ppm. Sklodowskite and carnotite represent the main uranium minerals detected in the face wall of the quarry with anomalous contents of gold. The gold content reaches 1.78, 1.74, 2.02, 1.6, 1.78 and 1.8 ppm in the ferruginous sandstone, dolostone, black shale, marl, claystone and gibbsite, respectively. The structure (faulting), lithology (carbonaceous material and clay minerals in addition to iron oxides), topography (low basin) and biogenic effects (organic matter) are the main factors that controlled the localization and concentration of the uranium and gold minerals within the Um Bogma Formation in the G. Alloga area, especially in Alloga Quarry. In addition to the secondary ascending hydrothermal solutions carry out the radioactive and gold minerals to deposit mainly along with fractures and faults.